2018
DOI: 10.1155/2018/6278501
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Fluoxetine in Four Children with Autistic Spectrum Disorder Improves Self-Injurious Behavior, ADHD-Like Symptoms, and Irritability

Abstract: Autism Spectrum Disorder (ASD) is defined by the copresence of two core symptoms: alteration in social communication and repetitive behaviors and/or restricted interests. In ASD children and adults, irritability, self-injurious behavior (SIB), and Attention Deficit and Hyperactivity Disorders- (ADHD-) like symptoms are regularly observed. In these situations, pharmacological treatments are sometimes used. Selective Serotonin Reuptake Inhibitors- (SSRI-) based treatments have been the subject of several publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Instead of seeing significant improvement in symptoms and/or behavior, the citalopram hydrombromide group experienced adverse effects of the drug, including increased energy level and hyperactivity, insomnia, reduced concentration, impulsiveness, and stereotyped behaviors. Recently, a case report in which four children 6–12 years old with ASD were given low doses of the SSRI fluoxetine found improvement in attention‐deficit/hyperactivity disorder‐like symptoms, irritability and/or self‐injurious behavior (Lucchelli and Bertschy ). Previously, Hollander et al () found improvement in repetitive behaviors in adult ASD subjects who were administered fluoxetine while McDougle et al (), in a clinical trial using the SSRI fluvoxamine, reported improvement in aggressive behavior in adult ASD patients.…”
mentioning
confidence: 99%
“…Instead of seeing significant improvement in symptoms and/or behavior, the citalopram hydrombromide group experienced adverse effects of the drug, including increased energy level and hyperactivity, insomnia, reduced concentration, impulsiveness, and stereotyped behaviors. Recently, a case report in which four children 6–12 years old with ASD were given low doses of the SSRI fluoxetine found improvement in attention‐deficit/hyperactivity disorder‐like symptoms, irritability and/or self‐injurious behavior (Lucchelli and Bertschy ). Previously, Hollander et al () found improvement in repetitive behaviors in adult ASD subjects who were administered fluoxetine while McDougle et al (), in a clinical trial using the SSRI fluvoxamine, reported improvement in aggressive behavior in adult ASD patients.…”
mentioning
confidence: 99%
“…Treatment with the SSRI fluoxetine rescued this phenotype in mice (35). Case reports of children aged 6 to 12 years treated with low-dose fluoxetine cited rapid and significant improvement in self-injurious behavior, hyperactivity, irritability, and impulsivity (36). A recent national survey reported a caregiver-perceived overall net benefit from treatment with sertraline, though significant individual response variation was also reported (37).…”
Section: Discussionmentioning
confidence: 99%
“…This can lend a start to reformulating behaviours seen in PDA as a profound manifestation of an underlying, functionally-impairing anxiety as opposed to a new distinct subtype of autism. Lucchelli et al, (2018) found that uoxetine can decrease self-injurious behaviours, ADHD-like symptoms and irritability at low doses in children with autism, but no studies have been conducted yet on the use of uoxetine for PDA [11]. This study aims to contribute to the understanding of PDA in autism and begin to build evidence for treatment with SSRI's as we hypothesize that PDA is likely a physical manifestation of anxiety.…”
Section: Pda -The Diagnostic Dilemmamentioning
confidence: 96%